A case study on using iPads to encourage collaborative learning in an undergraduate web development class - Loizides, Fernando; Souleles, Nicos; Mavri, Aekaterini (My University, 2014)
Since its release in 2010 the iPad has become the leading computer tablet in the market. Due to its popularity, the iPad is widely used in different higher education (HE) institutions around the world. However, the research on the use of this tablet in HE remains limited. This paper describes how the iPad was used in an undergraduate web development class to encourage collaboration through participatory exercises. Firstly, the students were provided with the tablet in order to contribute to the class exercise, and then the iPad display was streamed real-time to a projector. The device was passed from student to student, thus bypassing the need for them to individually walk up to the lecturer's computer. This instructional approach also eliminated the use of laptops or workstations, and encouraged collaborative and active learning. Data was gathered through surveys and interviews with participating students, and a mixed methods approach was applied to the analysis. This paper reports on the user experience and the perceived learning outcomes, as well as the advantages and disadvantages of using this instructional approach for the specific lesson.
Keywords: Active learning; Collaborative learning; Programming; Web development